Waste and Recycling : Theory and Empirics. - Shinkuma, Takayoshi (Taylor & Francis, 2011)
Waste generation, source reduction and recycling are matters of concern in today's world. The book discusses how economics can contribute to solve environmental problems and studies the waste reduction and recycling problems both theoretically and empirically, covering not only traditional resource economics and waste management, but also recent problem of Electric waste (E-waste) and recycling.